Relationship Between Types Of Employee’s Benefits (Leave, Health/Medical Insurance, Allowance, And Flexible Working Schedule) And Employee’s Retention - Nurul Syahmila, Sadiman (Universiti Malaysia Sarawak, (UNIMAS), 2021)
Organization now struggling in maintaining their employees with minimum resources. This study is to determine the relationship types of employee’s benefits (leave, health/medical insurance, allowance, and flexible work schedule) and employee’s retention. Employees from 2 SME have been chosen as respondent in this study and data were analysed using 2 types of testing statistically relationship which is Pearson Correlation Coefficient and Multiple Regression Analysis. Allowances and health/medical insurance performed the most significant relationship with employee’s retention rather than leave and flexible work schedule. It can be assumed that the money and health the factors that can influence employee behaviour and attitudes in organization.